Hippocampus RNA Sequencing of Pentylenetetrazole-Kindled Rats and Upon Treatment of Novel Chemical Q808 - Li, Xiang; Wang, Qing; Zhang, Dian-wen; Wu, Di; Zhang, Si-wei; Wei, Zheng-ren; Chen, Xia; Li, Wei (Frontiers in Pharmacology, 2022)
The expression of genes altered in epilepsy remains incomplete, particularly in the hippocampus, which exhibits exquisite vulnerability to epilepsy. Q808 is an innovation chemical compound that has potent anti-convulsant effect. Exploring its mechanism can not only explore the pathogenesis of epilepsy, but also provide a theoretical basis for its clinical application. The present study aimed to use RNA sequencing (RNA-seq) to reveal the gene transcriptomic profile of chronic pentylenetetrazole (PTZ)-kindled seizure rats and the difference of the PTZ model rat before and after treatment with Q808. Quantitative real-time PCR (qRT-PCR) was performed to validate the RNA-seq results. Protein level was estimated with Western blot. Hippocampal transcriptomic analysis showed that 289 differentially expressed genes (DEGs) were confirmed in the PTZ-kindled seizure group compared with the vehicle control. Gene cluster analysis identified most of the DEGs linked to neuronal apoptosis, neurogenesis, neuronal projections, and neurotransmitter regulation. After analysis across the three groups, 23 hub genes and 21 pathways were identified, qRT-PCR analysis confirmed that most of the mRNA levels of hub genes were consistent with the RNA-seq results. Q808 treatment increased the level of ACE, a GABA-related protein. Our analysis showed the comprehensive compendium of genes and pathways differentially expressed for PTZ-kindled seizure rats and upon Q808 treatment in PTZ-kindled seizure, which may provide a theoretical basis to explore mechanism and unique efficacy of Q808 and the pathophysiology of epilepsy in the future.